Analisis Wacana Kritis Model Teun A. van Dijk pada Surat Kabar Online Kompas dengan Tajuk “Digembleng Empat Hari di Gunung Tidar, Kabinet Merah Putih Akan Bermalam di Tenda” - Wijayanti, Aurelia Rani (Indonesian Journal of Applied Linguistics Review, 2025)
Online newspapers offer the latest news with the aim of providing information and offering opinions to the public. One of them is news about the red and white cabinet that will hold a retreat at Mount Tidar, the article was published on October 23, 2024. This research uses descriptive qualitative approach with Teun A. van Dijk's theoretical approach. Data collection methods through documentation techniques and text observation. The purpose of this research is to find three main dimensions, namely superstructure, macro structure, and micro structure. The superstructure includes coherence and text scheme; the macro structure focuses on the theme and topic, namely the semi-military training of the Merah Putih Cabinet; while the micro structure includes elements such as setting, details, intent, presumption, as well as the use of sentences, coherence, pronomina, lexicon, graphics, and metaphors. The results of the analysis show that this article is designed to build a narrative about the discipline and togetherness of the cabinet by combining symbolic and technical aspects, which reflect the government's vision to face future challenges.